2023
DOI: 10.1038/s41526-023-00286-z
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational effects on fibroblasts’ function in relation to wound healing

Abstract: The spaceflight environment imposes risks for maintaining a healthy skin function as the observed delayed wound healing can contribute to increased risks of infection. To counteract delayed wound healing in space, a better understanding of the fibroblasts’ reaction to altered gravity levels is needed. In this paper, we describe experiments that were carried out at the Large Diameter Centrifuge located in ESA-ESTEC as part of the ESA Academy 2021 Spin Your Thesis! Campaign. We exposed dermal fibroblasts to a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Fibroblasts exhibit high sensitivity to SMG, which validates the possible significance of the TGF-β1/Smad3 signaling pathway in regulating wound healing [20]. A recent study revealed that changes in fibroblast structures and delayed cell migration were the main effects of altered gravity, contributing to alterations in the fibroblasts' function related to wound healing [21]. These studies indicated the gravisensitivity of mouse fibroblasts to SMG, suggesting that these cells are suitable for assessing the influence of microgravity on characteristics such as proliferation, function, and morphology.…”
Section: Discussionmentioning
confidence: 58%
“…Fibroblasts exhibit high sensitivity to SMG, which validates the possible significance of the TGF-β1/Smad3 signaling pathway in regulating wound healing [20]. A recent study revealed that changes in fibroblast structures and delayed cell migration were the main effects of altered gravity, contributing to alterations in the fibroblasts' function related to wound healing [21]. These studies indicated the gravisensitivity of mouse fibroblasts to SMG, suggesting that these cells are suitable for assessing the influence of microgravity on characteristics such as proliferation, function, and morphology.…”
Section: Discussionmentioning
confidence: 58%